The approach of foot drop in the primary health care: a case report (Portuguese Journal of Family Medicine and General Practice, 2021)
Introduction: Foot drop is defined by the inability to elevate the foot due to diminished strength of the dorsiflexor muscles. To elaborate a treatment plan, it is necessary to determine its etiology. Thus, the family doctor must recognize the situations in which the management of foot drop can be done exclusively in primary health care, differentiating from those that may require observation and assessment in-hospital care.Case description: 71-year-old man with arterial hypertension and dyslipidemia, medicated with indapamide. An appointment with the family doctor referred that, two days ago, had remained seated for two hours with the right leg crossed over the contralateral lower limb. By getting up, the patient noticed right foot numbness and inability to elevate the same foot. At the physical examination, he presented a steppage gait, with right foot drop and decreased sensitivity of the back of the foot. It was requested electromyography, which documented severe axonal damage of the right common peroneal nerve below the fibular neck, compatible with prolonged compression. The patient was submitted to physiotherapy sessions, demonstrating complete clinical resolution of foot drop after three months.Comment: The neuropathy of the common peroneal nerve is the main cause of foot drop and the third most frequent focal neuropathy, after the median nerve and cubital nerve. Compression remains the most frequent etiology. The most affected site is at the level of the fibular neck, manifested by steppage gait, consequent to decreased strength of the dorsiflexor muscles of the foot. Even though the diagnosis is usually clinical, most of the patients require electromyography. The initial treatment tends to be conservative, with a frequent resolution of the complaints in three months. This is a condition that may be uncommon in family medicine’s clinical practice, but its approach could be, many times, managed in primary health care. It is important to know how to reassure the patients about the semiology, therapeutic approach, and prognosis.
Keywords: Foot drop; Common peroneal nerve; Steppage